The future of eco-friendly cold mix asphalt. (October 2021) - Shanbara, Hayder Kamil; Dulaimi, Anmar; Al-Mansoori, Tariq; Al-Busaltan, Shakir; Herez, Manar; Sadique, Monower; Abdel-Wahed, Talaat
Abstract: Road pavements are pivotal to the infrastructure, transportation and ultimate efficiency of both the public and the economy. However, they are undeniably having detrimental effects on an already compromised environment. Consequently, a re-think about road pavement construction materials is of paramount importance. Cold mix asphalt (CMA) is a low carbon manufacturing approach to the production of flexible pavement material that has proved to be very promising, both economically and ecologically. This technology allows the manufacture of mixtures at ambient temperatures without heating huge amounts of aggregates and bitumen, this decreasing CO2 emissions and saving energy. In spite of these positive impacts, CMA has a high sensitivity to traffic and environmental stresses due to the existence of water within the mixture, this of major concern to the industry. This study aims to review types of CMA and the main developments involved in cold bitumen emulsion mixture (CBEM) technology that can be used without decreasing in-service performance. This review also aims to provide a practical guide for the manufacture of bitumen emulsion and the design procedure of CBEM for the road pavements industry. Finally, it can be suggested that CMA is a crucial technique for pavement construction, as it provides acceptable performance alongside energy-saving and ecological objectives. Highlights: CBEMs have several ecological and economic benefits. Laboratory data show an equal or better performance of CBEM compared to HMA. The laboratory behaviour investigations on CBEM are not conclusive. The application of waste materials in CMA improves sustainability.